Assessment of antigen presenting cell infiltration in lung tissues of patients with bronchiectasis - Waseem M Hajjar; Abdulaziz H Alzeer; Amany A Fathaddin; Hadil A Al-Otair; Ammar C Al-Rikabi; Zahid Shakoor (Wolters Kluwer Medknow Publications, 2016)
Background: Bronchiectasis is a chronic disease characterized by permanent dilatation of the conducting airways accompanied by sustained inflammation. Aims: To assess whether chronic inflammation of lungs in bronchiectasis is associated with alterations in the numbers of infiltrating antigen presenting cell (APC). Setting and Design: Lobectomy specimens from 12 nonsmoker, nonasthmatic patients with acquired (noncongenital) bronchiectasis and six control patients were included in the study. Histopathology slides were reviewed, and immunohistochemical markers for dendritic cells (DCs) macrophages and Langerhans cells have been applied and analyzed. Materials and Methods: Tissue specimens were stained by immunohistochemistry using markers for DCs (CD83 and CD23), macrophages (CD68 and CD163), and Langerhans cells (CD1A and S-100 protein). The mean cell counts of stained cells in five high power microscopic fields were recorded. Statistical Analysis Used: Descriptive statistics, mean, standard deviation, median, and interquartile range were used. A nonparametric Mann-Whitney U-test was used to compare cell counts between bronchiectasis and control patients. P <0.05 was considered significant. Results: The mean age of patients with bronchiectasis and controls was 36.7 ± 16.6 and 31.8 ± 22.6 years, respectively. The predominant cell type among the patients was macrophage (median 50.5) followed by DCs (median 44.85), histiocytes (median 32), and Langerhans cells (median 5%). Compared to the controls a significantly higher number of macrophages (P = 0.01), DCs (P = 0.001), and Langerhans cells (P = 0.014) were present. Conclusion: Chronic inflammatory response in acquired (noncongenital) bronchiectasis is most probably mediated by increased infiltration of APCs in lung tissues.